2016
DOI: 10.1007/s10519-016-9823-1
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of Behavioral Problems in 7-Year Olds Based on Shared and Unique Aspects of Parental Views

Abstract: In studies of child psychopathology, phenotypes of interest are often obtained by parental ratings. When behavioral ratings are obtained in the context of a twin study, this allows for the decomposition of the phenotypic variance, into a genetic and a non-genetic part. If a phenotype is assessed by a single rater, heritability is based on the child’s behavior as expressed in the presence of that particular rater, whereas heritability based on assessments by multiple raters allows for the estimation of the heri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…The current study also did not find a shared family effect (reflecting the influence of the other parent and the shared family environment) on depression or anxiety symptoms, within the pedigree‐based analyses. Within previous research, estimates of variance explained by the common family environment are broad and range from 0 to 0.32 (Fedko et al, 2017; Polderman et al, 2015; Wesseldijk et al, 2017). The ability to detect the effect varies, depending on the population and sample size.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The current study also did not find a shared family effect (reflecting the influence of the other parent and the shared family environment) on depression or anxiety symptoms, within the pedigree‐based analyses. Within previous research, estimates of variance explained by the common family environment are broad and range from 0 to 0.32 (Fedko et al, 2017; Polderman et al, 2015; Wesseldijk et al, 2017). The ability to detect the effect varies, depending on the population and sample size.…”
Section: Discussionmentioning
confidence: 98%
“…So far, knowledge on genetic and environmental parental influences on offspring internalizing symptoms has largely relied on twin and family based designs rooted in quantitative genetics. Findings from 50 years of twin research estimate that ~40% of the variance within individual differences in childhood internalizing problems is due to genetic factors and up to ~36% is due to the common family environment, which encompasses parental factors that account for similarities within the offspring (Fedko et al, 2017; Polderman et al, 2015; Wesseldijk et al, 2017). The remaining variance is explained by unique environment effects (unshared between twins and siblings), which can also include parental factors.…”
Section: Introductionmentioning
confidence: 99%
“…So far, twin studies have demonstrated that genetic differences between children explain about 52-78% of the differences in parent-reported behavioral problems in children. Shared environmental factors account for about 1-36% of the differences in childhood behavioral problems [13][14][15][16][17][18][19]. In addition, twin studies have shown that the contribution of genetic and environmental factors to individual differences in childhood behavioral problems varies across SES strata, indicating a moderator effect of SES on the genetic architecture of childhood behavioral problems.…”
Section: Introductionmentioning
confidence: 99%
“…Twin research suggests that variation in the part of children’s behaviour that raters see in common captures more of the genetic action than rater-specific variation 27 . For example, two studies found higher twin heritability for rater-common than rater-specific parts of variance in childhood anxiety (~46% vs ~17%) 28 , 29 . Further, the substantial covariation between anxiety and depression in childhood and adolescence is largely genetically influenced 10 , 30 .…”
Section: Introductionmentioning
confidence: 99%